Experimental evaluation of vortex generator usage to reduce the coefficient of drag of proton saga car - Aizad Ayasyi, Ab Ghafar (2007)
Proton Saga is one of the most successful sedan cars in Malaysia. The aerodynamics of this car can be defined as bad because the box shape gives a great value of drag coefficient. The improvement of the aerodynamics of Proton Saga car can reduce the fuel consumption because the power needed to withstand the drag force created is decreased. Economical effective wool tufts method is use to analyze the airflow of Proton Saga car with vortex generator. The increase of pressure distribution on the rear window surface of the car makes the flow separation to delay. The aerodynamics improves with the changes of most turbulence flow into laminar flow. The prediction that can be made that the drag force created decrease proportionally with the drag coefficient. This paper presents the analysis of the effect of vortex generator usage on delaying flow separation of Proton Saga car experimentally.